On the use of the operator product expansion in finite-energy sum rules for light-quark correlators - Diogo Boito, Maarten Golterman, Kim Maltman, Santiago Peris (SciPost Physics Proceedings)
Tau-based finite-energy sum-rule (FESR) analyses often assume that scales $s_0\sim m_τ^2$ are large enough that (i) integrated duality violations (DVs) can be neglected, and (ii) contributions from non-perturbative OPE condensates of dimension $D$ scale as $(Λ_{QCD}/m_τ )^D$, allowing the OPE series to be truncated at low dimension. The latter assumption is not necessarily valid since the OPE series is not convergent, while the former is open to question given experimental results for the electromagnetic, $I=1$ vector ($V$), $I=1$ axial vector ($A$) and $I=1$ $V+A$ current spectral functions, which show DV oscillations with amplitudes comparable in size to the corresponding $α_s$-dependent perturbative contributions at $s\sim2-3$ GeV$^2$. Here, we discuss recently introduced new tools for assessing the numerical relevance of omitted higher-$D$ OPE contributions. Applying these to the "truncated OPE" strategy used in Refs. [M. Davier et al., Eur. Phys. J. C 74, 2803 (2014); A. Pich and A. Rodríguez-Sánchez, Phys. Rev. D 94, 034027 (2016)] and earlier work by the same authors, we find that this strategy fails to yield reliable results for the strong coupling from hadronic $τ$ decays.